The Basics of Ultrasonography (Bangladesh Medical Journal, 2017)
Ultrasound is sound whose frequency is above the human hearing range. It is nowadays widely used for the evaluation of a patient’s internal organs. Ultrasound waves are transmitted into the human body by an instrument called the transducer. Inside the body the sound waves are reflected and scattered differently by the different tissues and organs. The reflected sound waves are used by the computer to form an image of the internal structures and tissues. Use of ultrasound is safe with negligible bio-effects.Bangladesh Med J. 2017 Jan; 46 (1): 44-47